Produção de juvenis de Artemia franciscana e análise da utilização de dietas vivas e inertes na larvicultura intensiva do pintado Pseudoplatystoma coruscans - Takata, Rodrigo [UNESP] (Universidade Estadual Paulista (Unesp), 2007)
The intensive cultivation of Artemia franciscana is an activity carried out in some countries with relative success; however this activity is not so expressive in Brazil. The aim of this work was to standardize the cultivation technology of Artemia juveniles in regions that are distant from the seashore, using only NaCl for salinization of the water and different diets, salinity rates and temperatures. One carried out three experiments by which the brans of soybeans, rice and wheat, fresh and dried yeast, grinded oat; salinity of 10‰, 20‰, 25‰, 30‰, 35‰ and temperatures of 20oC, 25oC and 30oC. The experimental period lasted for ten days in every experiment, and the feeding was done twice a day, offering 0,2g/L from the first until the sixth and 0,35g/L from the seventh to the tenth day. The survival rate and biomass production were also evaluated. The soybean bran did not show satisfactory results, being that not a single live Artemia was found in this treatment after the experimental period. However, on the other treatments, one observed the same tendencies for the survival as well as for biomass production, with a distinction to the oat bran treatment that came to be statistically superior compared to the other diets. In the salinity experiment, no live Artemia were observed after ten days of cultivation at a concentration of 10‰. Both 30‰ and 35‰ salinity rates outstood (P<0,05) over the 20‰ and 25‰ concentrations, which did not present any differences among each other (P>0,05). Regarding the temperature, the best averages for survival were obtained with an intermediate temperature (25oC); however not different (P>0,05) from the highest temperature (30oC). The 20oC temperature presented statistically inferior (P>0,05) survival and biomass production rates in comparison to the other temperatures...

O cultivo intensivo da Artemia franciscana é uma atividade praticada em alguns países com relativo êxito; no Brasil, essa atividade é pouco expressiva. O objetivo do trabalho foi padronizar tecnologia de cultivo de juvenis de Artemia em regiões distantes do mar, utilizando apenas NaCl para salinização da água e diferentes dietas, salinidades e temperaturas. Foram realizados três experimentos: no primeiro foram avaliados os alimentos (farelos de soja, de arroz e de trigo, levedura fresca e seca e aveia triturada); no segundo, as salinidades (10‰, 20‰, 25‰, 30‰ e 35‰) e no terceiro as temperaturas (20°C, 25°C e 30°C). O período experimental foi de 10 dias em todos os experimentos, a alimentação dos animais foi fracionada em duas vezes ao dia, e a quantidade de alimento oferecida foi de 0,2g/L do 1° ao 6° dia e de 0,35g/L do 7° ao 10° dia. Foram determinadas a sobrevivência e a produção de biomassa. O farelo de soja não apresentou bons resultados, sendo que ao final do experimento nenhuma Artemia foi encontrada viva nesse tratamento. Contudo, nos demais tratamentos, observaram-se as mesmas tendências tanto para a sobrevivência quanto para a produção de biomassa, com destaque para a dieta de aveia que foi estatisticamente superior às demais dietas. No experimento de salinidade não foram observadas Artemia vivas após 10 dias de cultivo na concentração de 10‰. As salinidades de 30‰ e 35‰ proporcionaram maiores taxa de sobrevivência diferenciando (P<0,05) das salinidades de 20‰ e 25‰, que não apresentaram diferenças entre si (P>0,05). Em relação à temperatura, melhores médias de sobrevivência foram obtidas com a temperatura de 25°C e 30ºC. A temperatura de 20°C apresentou taxas de sobrevivência e produção de biomassa estatisticamente inferiores (P<0,05) às das demais temperaturas...
Keywords: Artemia; Crustaceo; Peixe - Alimentação; Larva; Aquicultura; Crustacea